Best-bet integrated strategies for containing drug-resistant trypanosomes in cattle - Mungube, E.O.; Diall, O.; Baumann, M.P.O.; Hoppenheit, A.; Hinney, B.; Bauer, B.; Sanogo, Y.; Maiga, B.; Zessin, K.H.; Randolph, Thomas F.; Clausen, Peter-Henning (Springer, 2012)
**Background**